Relating indigenous knowledge practices and science concepts : an exploratory case study in a secondary school teacher-training programme - Mandikonza, Caleb (Rhodes University, Faculty of Education, Department of Education, 2007)
This study reports research on how student teachers in Science at Mutare Teachers' College in Zimbabwe worked with indigenous knowledge practices in relation to science concepts in the secondary school syllabus. The study was conducted among first-year science students and involved them in developing science learning activities for a peer-teaching process that was part of their course. The research was undertaken during a review ofthe college syllabus and as a study to inform the Secondary Teacher Training Environmental Education Programme (STÂ²EEP). The research design involved the researcher in participant observations and interviews with rural people to document indigenous knowledge practices and to develop materials for the students to work with in the lessons design part of the study. The student teachers used the documented practices to generate learning activities and lesson plans to teach the science concepts they had identified. A peer review session and focus group interviews followed the lesson presentations. Findings from the research point to the rural community being a repository of diverse indigenous knowledge practices. Student teachers showed that they had prior knowledge of both indigenous knowledge practices and science concepts when they come to class. Student teachers were able to relate indigenous knowledge practices and science concepts in ways that have the potential to enhance the learning of science in rural school contexts that lack laboratories and science equipment. The scope of the study does not allow for anything beyond tentative conclusions that point to the need for further work to be undertaken with student teachers and for the research to be extended to teaching and learning interactions in schools. Recommendations are also made for further resource-based work to be undertaken within the forthcoming StÂ²eep implementation phase in 2007.
Keywords: Ethnoscience -- Study and teaching (Secondary) -- Zimbabwe; Science -- Study and teaching (Secondary) -- Zimbabwe; Teachers -- Training of -- Zimbabwe